TERORISME SEBAB DAN PENANGGULANGANNYA - Semjan Putra, Ali Musri (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2014)
One of the world problems that do not have definite solutions yet is terrorism. There were already many conferences and seminars held, but all of them were just ended with theories. In this paper, I am trying to discuss this problem from the point of view of my expertise, the Islamic creed. Theories proposed by many experts still do not meet the standards of excellent, according to my opinion, since their analyses focus on the effects of terrorism only. It is very rare to find a discussion about terrorism from the point of view of its causes that provoke this grave action. Also, many other analyses put their focuses on the solutions of terrorism in the form of movement. It is very hard to find the one that talks about the ideological solutions. According to my opinion, terrorism will not be eliminated by using weapons because they, the terrorists, are not afraid of the death. Therefore, in this paper, I am trying to discuss the ideological solutions to solve the problem of terrorism. Keyword: terrorism, causes, solutions, prevention